White, Sclerotic Lesions of the Head, Neck, and Fingers. Issue 5 (September 2017) - Masoud, Melanie; Wahjudi, Ingrid; Moncrieff, Norma; Jacob, Sharon E.
Abstract : ABSTRACT: The patient presented here is a 68-year-old man with mildly itchy white lesions on the head, neck, and fingers for 7 years. This article guides the reader to identify a diagnosis based on the symptoms and appearance of the lesions, discusses the differential diagnoses, and presents the diagnosis and treatment plan.